Highly dispersed Ni-Ce catalyst over clay montmorillonite K10 in low-temperature CO2 methanation - Francesco Nocito; Nicoletta Ditaranto; Angela Dibenedetto (Journal of CO2 Utilization)
The Carbon Capture and Utilization (CCU) option can be an efficient solution for CO2 emission mitigation. To this end, we have investigated the carbon dioxide methanation at low temperatures. Highly active, selective, stable, low-cost catalysts are required for energy and carbon balance benefits. Supported nickel-based catalysts result as the most studied and promising candidates showing a good compromise between performance and low preparation costs. The catalyst design role is key to obtaining the best performance, requiring many experiments and optimisation procedures. Herein, the enhanced Montmorillonite MK10-supported Ni(0)Ce(III) catalyst, prepared by consecutive hydrothermal and electrostatic adsorption methods followed by reduction under hydrogen flow, was used in batch CO2 methanation, exhibiting 76 % of CO2 conversion with 100 % CH4 selectivity after 3 h. The catalytic system reveals very high robustness preserving the same activity and selectivity for at least 5 reaction cycles if compared with γ-Al2O3-supported Ni(0)Ce(III) catalyst, the latter showing the same activity but only in the first cycle. EDX, XPS, SEM, TPD, TPR, and BET characterisation techniques were used to elucidate and evaluate the potential synergistic effect of the active metal centre-promoter-support interfaces, highlighting their role in the activity and robustness of the catalyst, comparing the same effect using different alumina and silicate solid supports. The effects of the reaction conditions on the methane yield and selectivity were also evaluated.